MODERN APPROACHES IN THE TREATMENT OF CHRONIC SINUSITIS (World Bulletin of Public Health, 2025)
Chronic sinusitis is one of the most common diseases of the paranasal sinuses, which has a significant impact on the patient's quality of life. According to statistics, this pathology affects a large number of people, and many of them experience relapses and long-term problems despite conservative treatment. In today's fast-paced world, where people often cannot afford to recover for extended periods, there is a growing need for effective and minimally invasive treatment methods. This is where endovascular treatment becomes an important and relevant tool.
Keywords: endovascular treatment; chronic sinusitis; minimally invasive methods